2018
DOI: 10.1002/jcb.26866
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid modulates fibroblast proliferation and differentiation in response to pro‐fibrotic stimuli

Abstract: In response to tissue injury, fibroblasts migrate into the wound, where they undergo proliferation and differentiation. The persistence of these differentiated fibroblasts (myofibroblasts) is associated with excessive scarring in various organs. We aimed to investigate the effects of Tannic acid (TA) on fibroblast proliferation and differentiation, and found that TA inhibited fibroblast differentiation as assessed by reduced expression of α-smooth muscle actin, N-cadherin, and type-1-collagen. TA also prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
(96 reference statements)
1
14
0
Order By: Relevance
“…Increasing the TA content in the hydrogels yielded a small decrease of cell viability from 90% for TAPS2 to 75% for TAPS8 hydrogel, probably due to the dose-dependent inhibition of TA on fibroblast proliferation. 46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the TA content in the hydrogels yielded a small decrease of cell viability from 90% for TAPS2 to 75% for TAPS8 hydrogel, probably due to the dose-dependent inhibition of TA on fibroblast proliferation. 46…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the TA content in the hydrogels yielded a small decrease of cell viability from 90% for TAPS2 to 75% for TAPS8 hydrogel, probably due to the dosedependent inhibition of TA on fibroblast proliferation. 46 Skin compatibility of the polySBMA and TAPS8 hydrogels was evaluated using the irritation test according to the standard protocol. No reaction signs of erythema or edema were observed on the animal skin after treatment (Fig.…”
Section: Cytotoxicity and Skin Compatibilitymentioning
confidence: 99%
“…Tannic acid (TA; chemical structure, C 76 H 52 O 46 ) is a specific type of tannin, which is a water-soluble polyphenol, and is a mixture of five galloyl esters and one glucose (25). Previous studies have indicated that TA possesses anticarcinogenic, antioxidant, antimutagenic, anti-inflammatory, antifibrotic and cardioprotective effects (26)(27)(28)(29)(30). To date, to the best of our knowledge, there are no published scientific reports on the effects of TA on LPS-induced myocardial injury or related ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Tannic acid (TA), a speci c type of tannin, is water-soluble polyphenols with a C 76 H 52 O 46 chemical structure, and is a mixture of ve galloyl esters and one glucose [27]. Previous studies have indicated that TA possesses anticarcinogenic, antioxidant, antimutagenic, anti-in ammatory, anti brotic, and cardioprotective effects [28][29][30][31][32]. To date, there are no published scienti c reports on the effects of TA on LPS-induced myocardial injury or related ailments.…”
Section: Introductionmentioning
confidence: 99%